PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOGNITIF DAN KETERAMPILAN BERPIKIR KRITIS MATERI IPA SISWA KELAS V SD DI KECAMATAN HERLANG KABUPATEN BULUKUMBA - Sarimuddin Sarimuddin; Muhiddin Muhiddin; Evi Ristiana (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON THE COGNITIVE ABILITIES AND CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTSResearch has been done with the aim to knowing there is or not a significant positive effect of the problem based learning model on student’s cognitive abilities and critical thinking skills. To achieve the aim, this research was carried out using Pretest-Postest Control Group Design of research which belongs to the type of true experiment research. The results of the study showed the students' cognitive ability data included parametric data groups so tested with Independent Sample T-Test and critical thinking skills of students including nonparametric data groups so tested with Mann-Whitney obtained significance scores of 0.04 and 0.04 or less than 0.05, meaning the hypothesis was accepted. Wilcoxon's follow-up test as a pretest-posttest rank comparison test between the control class and the experiment showed that the experimental class's significance scores of both cognitive ability and critical thinking skills of students were 0.00 and 0.00 or less than 0.05, respectively, and included smaller than the significance of the control classes of 0.11 and 0.03 respectively which meant the hypothesis was accepted. Thus it can be concluded that there are a significant positive influence of the Problem Based Learning model on students' cognitive abilities and critical thinking skills.